2009
DOI: 10.1002/prot.22624
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐scale characterization of the energy landscape of proteins with application to the C3D/Efb‐C complex

Abstract: We present a novel multi-level methodology to explore and characterize the low energy landscape and the thermodynamics of proteins. Traditional conformational search methods typically explore only a small portion of the conformational space of proteins and are hard to apply to large proteins due to the large amount of calculations required. In our multi-scale approach, we first provide an initial characterization of the equilibrium state ensemble of a protein using an efficient computational conformational sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…While the contributions of specific positions in C3d have not yet been examined by mutagenesis, this type of detailed structure/function analysis has been carried out for Efb-C (Hammel et al 2007b; Haspel et al 2010; Haspel et al 2008). This work has demonstrated that positions R131 and N138 of Efb-C are particularly critical determinants for both the affinity and stability of the C3d complex.…”
Section: Recent Developments Regarding the Extracellular Fibrinogenmentioning
confidence: 99%
See 1 more Smart Citation
“…While the contributions of specific positions in C3d have not yet been examined by mutagenesis, this type of detailed structure/function analysis has been carried out for Efb-C (Hammel et al 2007b; Haspel et al 2010; Haspel et al 2008). This work has demonstrated that positions R131 and N138 of Efb-C are particularly critical determinants for both the affinity and stability of the C3d complex.…”
Section: Recent Developments Regarding the Extracellular Fibrinogenmentioning
confidence: 99%
“…Studies on both single and pairwise substitutions at positions 131 and 138 revealed that interactions between Efb-C and C3d are dependent upon both the charge and polar nature of these side chains. Whereas the observed K D rose to 26 and 19 nM, respectively, when either residue alone was mutated to alanine (Haspel et al 2010; Haspel et al 2008), the corresponding double mutant had no residual affinity (Hammel et al 2007b; Haspel et al 2008). Furthermore, while loss of the side chain functionality had only minor effects on the ionic strength-dependent association phase, the rate of complex dissociation was greatly accelerated in each mutant (Haspel et al 2008).…”
Section: Recent Developments Regarding the Extracellular Fibrinogenmentioning
confidence: 99%
“…14 Furthermore, later studies thoroughly investigated the characteristics of these mutants in comparison to wild-type EfbC. 15,16 In accordance with the two-step binding model of protein association, the results of surface plasmon resonance experiments indicated that these mutants have little effect on association rates, but drastically increase dissociation rates for the complex with C3d. This indicates that highly-specific interfacial interactions are responsible for maintaining complex stability, while complex association is governed by the overall electrostatic potential distributions of C3d and EfbC.…”
Section: Electrostatic Association and Binding Of C3d-efbc And C3d-ehpmentioning
confidence: 60%